Transherniary approach to laparoscopic cholecystectomy - Pose, Juan; Hermida, Mario; Berhouet, Horacio; Delgado, Fernando (Cirugía del Uruguay, 2000)
Laparoscopic approach is currently the elective approach in the treatment of non-complicated biliary lithiasis. There was a time when an umbilical herniation presented a series of problems at the time of deciding on the approach to be taken.